A Comparative Evaluation of Gross Non-Performing Assets of Listed Public Sector and Private Sector Banks in India: An Empirical Study - MEGHA G; BHARATH V (Advanced International Journal of Multidisciplinary Research, 2026)
Non-Performing Assets (NPAs) are one of the major factors which ascertain the financial health and asset quality of banks. A high level of NPAs has a negative impact on profitability, liquidity, lending capability and financial stability. Over the past decade, significant reforms have taken place in the Indian banking sector, leading to enhanced credit monitoring, recovery procedures, and regulatory oversight. Nevertheless, there is continued variation in performance of Public Sector Banks (PSBs) and Private Sector Banks (PVBs) on asset quality and Credit Risk Management. The aim of the present study is to assess and compare the Gross Non-Performing Assets (Gross NPA %) of selected Public Sector Bank and Private Sector Bank in India during 2019-20 and 2023-24. The study has been done on secondary data obtained from published annual report and financial statement of ten leading banks of the country which include five Public Sector Banks (State Bank of India, Canara Bank, Punjab National Bank, Karnataka Bank and Bank of Baroda) and five Private Sector Banks (ICICI Bank, HDFC Bank, Axis Bank, Kotak Mahindra Bank and IndusInd Bank). To explore the trend and variability of Gross NPAs, descriptive statistics were used. The asset quality performance of the two banking sectors was compared through the Independent t test. The results indicated a higher Gross NPA ratio in the Public Sector Banks during the entire period under study than the corresponding of Private Sector Banks. The results of Independent t test showed that there is statistically significant difference between Gross NPA percentage of the two groups (p < 0.001) thus suggesting that the Private Sector Banks displayed better Asset Quality and Credit Risk Management. The study is important in the literature because it brings up to date comparative evidence on the performance of NPAs in the banks post major banking reforms and emphasizes on the need for enhancing credit appraisal, monitoring and recovery mechanism in the Public Sector Banks.